IMPLEMENTASI ALGORITMA DIFFIE-HELLMAN KEY EXCHANGE (DHE) DAN AES DALAM ENKRIPSI PESAN END-TO-END - M. Khairi Nasution; Rachmat Aulia; Antoni (PT. Hasba Edukasi Mandiri, 2025)
Digital communication security is a crucial aspect in the modern era of information technology. This study aims to implement a combination of the Diffie- Hellman Key Exchange (DHE) and Advanced Encryption Standard (AES) algorithms in an end- to-end encryption (E2EE) system to ensure data confidentiality and integrity. The method used includes a secure key exchange process via the DHE algorithm and message encryption using AES-256, ensuring secure communication between two users. The research process began with the design of a web-based communication system that allows users to securely exchange messages. The initial stage involves the exchange of public keys between two parties using DHE, which then generates a shared secret key. This key is subsequently used in the encryption and decryption of messages using AES, strengthened by the use of an Initialization Vector (IV) to enhance security. An example of implementation is demonstrated through a communication simulation between Alice and Bob, where values of p = 23 and g = 2 are used as public parameters, while a = 6 and b = 15 serve as private values. Both parties successfully establish a shared key of 4, which is then used to encrypt a message such as “Hello, Bob!” into ciphertext. This message can only be decrypted by the recipient using the same key and the included IV. With this system, users can securely send and receive text messages through a simple yet functional interface.